Language Diversity and Performance in International Teams: A Qualitative Research - Sand, Susanne (My University, 2023)
As the business environment has become ever more internationalized, cross-cultural interaction has proliferated, and many organization members have encountered issues related to linguistic diversity. Organizations seeking a competitive advantage must pay increasing attention to how they manage language and communication. For many firms, business communication rests on language skills, without which the right information may not reach the people for whom it is intended. As well as enabling the communication of information, language facilitates value creation through the exchange of ideas; hence, it is a vital element of development. The thesis aims to comprehend the connection between language diversity and performance, including how the uncertainty reduction theory; clustering, cultural intelligence, and linguistic competency affects performance in teams, as well as how language diversity is managed. By conducting 10 interviews, a qualitative methodology is used to investigate this area within one multicultural team. The respondents are currently in various roles within a multilingual and multicultural team, working across the EMEA region. The results imply that there is an association between language diversity and performance, which could be improved by implementing a language management policy and using tools and solution strategies within the team and organization. Nevertheless, there is still significant resistance to the change from local offices. Another crucial aspect of linguistic diversity and improved performance would be to hire a more diverse workforce and clearly communicate the language policies within the teams and company. Therefore, establishing transparency and unambiguous communication from top management should be a goal for organizations.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business